Dipotassium glycyrrhizinate relieves leptospira-induced nephritis in vitro and in vivo. (March 2021) - Lv, Tianbao; Wu, Dianjun; Song, Ning; Zhang, Shilei; He, Siwei; Wang, Jiaqi; Ding, Yue; Zhang, Wenlong; Cao, Yongguo
Abstract: Chronic leptospirosis usually occurs during sublethal doses infection of susceptible animal and reservoir host, which typical symptom is interstitial nephritis, and leptospira urine, contaminating the environment and threatening other susceptible animals and humans. Dipotassium glycyrrhizinate (DG) is a replacement for glycyrrhizic acid, which exhibits anti-inflammation, immunomodulation effects. This study is to investigate whether DG relieves leptospira-induced nephritis. In vitro, DG inhibited the leptospira-induced transcription levels of IL-1β, IL-6, TNF-α, RANTES, MCP-1 and iNOS, and protein levels of IL-1β and TNF-α, and downregulated NF-κB and MAPK pathway in TCMK-1 cells. In vivo, DG attenuated the kidney histopathological change and downregulated the expression of IL-1β and TNF-α, as well as reduced kidney leptospiral burden. In summary, DG alleviated leptospira-induced inflammation through inhibitory NF-κB and MAPK pathway, and DG decreased the renal colonization of leptospires in mice. Highlights: DG downregulates the expression of cytokines and chemokines in leptospira-infected TCMK-1 cells. DG inhibits the NF-κB and MAPK signaling pathways activation caused by leptospira-infection in vitro . DG alleviates leptospira-induced nephritis in chronic leptospirosis model. DG reduces the colonization of leptospires in mice.